Near-infrared light-mediated rare-earth nanocrystals: recent advances in improving photon conversion and alleviating the thermal effect. (August 2018) - Lyu, Linna; Cheong, Haolun; Ai, Xiangzhao; Zhang, Wenmin; Li, Juan; Yang, HuangHao; Lin, Jun; Xing, Bengang
Abstract With the rapid development of nanotechnology, the unique rare-earth lanthanide-doped upconversion nanocrystals (UCNs), which can convert tissue-penetrable near-infrared (NIR) photonic irradiation into ultraviolet, visible, and NIR emissions, have a significant potential in bioimaging, diagnosis, and therapy, as well as in photovoltaic systems and optical data storage. Despite the promising achievements made in the past decade, critical challenges associated with low upconversion efficiencies and the overheating effect induced by NIR laser-irradiation still remain in the biomedical fields. In high demand are more well-defined material design and unique structural modifications that are capable of solving these technical concerns and promoting such promising NIR light-mediated upconversion nanocrystals for their further application in the medical sciences. Recent advances in upconversion nanomaterials have witnessed a tremendous development towards enhancing their photon conversion efficiency, which provides great opportunities in expanding the potential of the UCNs in bioimaging diagnosis and anticancer therapy. Hence, this review is mainly focused on summarizing the fundamental principles and strategies that improve upconversion luminescence and the approaches to reduce the local thermal effect on the basis of a rational design of UCNs. In addition, the future perspectives in the development of UCNs for biomedical applications are also proposed. Nanocrystals: helping bright bioprobes keep their cool Rare-earth elements and organic dyes are improving the safety and efficiency of innovative fluorescent probes designed to diagnose tumors and other disorders deep inside living tissue. Upconversion nanocrystals are microscopic particles that can release a broad range of infrared, visible, and ultraviolet light after activation by laser irradiation. Bengang Xing from Nanyang Technological University in Singapore and colleagues review how these nanomaterials may be engineered to achieve brighter luminescence while minimizing laser-related heating. Although researchers normally impregnate upconversion nanocrystals with small amounts of rare earths, new findings show that boosting rare earth levels with ions such as neodymium enables the tuning of laser excitations to biologically compatible frequencies, and emission outputs to specific colors. Adding organic molecules capable of broadband light adsorption to the nanocrystals offers opportunities for targeted, ultra-bright imaging and activation of biomolecules. With the rapid development of nanotechnology, the unique rare earth lanthanide-doped upconversion nanocrystals (UCNs), which can convert tissue-penetrable near-infrared (NIR) photonic irradiation into ultraviolet, visible and NIR emissions, have found significant potential in bioimaging, diagnosis, therapy, as well as photovoltaics and optical data storage. Despite the promising achievements made in the past decade, critical challenges associated with low upconversion efficiencies and overheating effect induced by NIR laser-irradiation remain in the biomedical fields. More well-defined material design and unique structural modification are highly demanded that are capable of solving these technical concerns and promoting such promising NIR light mediated upconversion nanocrystals for their further practice in medical sciences. Recent advances in upconversion nanomaterials have witnessed the tremendous development towards enhancing the photon converted efficiency, which provides great opportunities in expanding the UCNs potential in bioimaging diagnosis and anticancer therapy. Hence, this review is mainly focusing on summarizing the fundamental principles and strategies to improve the upconversion luminescence and the approaches to reduce the local thermal effect on the basis of rational design of UCNs. In addition, the future perspectives in the development of UCNs for biomedical applications are also proposed.